Reference management: A critical element of scientific writing - Kali, Arunava (J Adv Pharm Technol Res, 2016)
With the rapid growth of medical science, the number of scientific writing contributing to medical literature has increased significantly in recent years. Owing to considerable variation of formatting in different citation styles, strict adherence to the accurate referencing manually is labor intensive and challenging. However, the introduction of referencing tools has decreased the complexity to a great extent. These software have advanced overtime to include newer features to support effective reference management. Since scientific writing is an essential component of medical curriculum, it is imperative for medical graduates to understand various referencing systems to effectively make use of these tools in their dissertations and future researches.